Metastatic endometrial stromal sarcoma: a case report - Pillai, Shobha S.; Govinda, Unnikrishnan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometrial Stromal Sarcoma (ESS) is a rare slow growing tumour of mesodermal origin arising from the stroma of the endometrium and accounting for less than 1% of all uterine cancers. It is characterized by late recurrences and distant metastases. This report presents a case of ESS in a 40 year old nulliparous woman who had a myomectomy for a clinically suspected Leiomyoma uterus in a local hospital. The histopathological examination of the specimen revealed ESS and the patient was referred to our tertiary institute. Here after investigations including a CT scan which also revealed pulmonary metastases, patient underwent Modified Radical Hysterectomy with Bilateral Salpingo-oophorectomy with pelvic lymph node sampling. Histopathological Examination of the uterine specimen confirmed the diagnosis. The patient was given the option of referral to a thoracic surgeon for resection of the isolated lung metastasis, but she refused this and opted instead for hormone therapy which she is presently undergoing. ESS is a very rare tumour often presenting with clinical and examination findings suggestive of leiomyoma of the uterus and hence misdiagnosed. In cases of rapidly growing tumours and suspicious radiological features, suspect sarcoma and initiate timely diagnosis and proper treatment. Recommended long-term follow up in view of late recurrences.